2020
DOI: 10.1007/s42058-020-00051-1
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone-based online tool for prehospital self-triage of COVID-19

Abstract: The COVID-19 epidemic has swept across China and spread to other countries. The rapid spreading of COVID-19 and panic combined with the lack of a hierarchical medical system in China have resulted in a huge number of hospital visiting which are overwhelming local medical system and increasing the incidence of cross infection. To meliorate this situation, we adopted the management concept of the system of Tiered Diagnosis and Treatment and developed an online tool for self-triage based on the mostly used multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
(9 reference statements)
2
9
0
1
Order By: Relevance
“…Labs peaked close to the onset of symptoms and colocalized with peak opacities. Even though this methodology was based on only a few longitudinal datasets (8/20 for LDH), it has been widely used previously to display this type of sparse data 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labs peaked close to the onset of symptoms and colocalized with peak opacities. Even though this methodology was based on only a few longitudinal datasets (8/20 for LDH), it has been widely used previously to display this type of sparse data 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has evaluated the temporal dynamics of CT features in patients with COVID-19, however, thus far has been focused on post-symptomatic timepoints 10 13 . Far less is known about the CT appearance in the pre-symptomatic period, nor how this relates to subsequent overall course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Tools studied were mostly located in the United States (6/22, 27%) [3,10,11,19,24,25]. A total of 12 studies were conducted in other countries, including France (3/12, 25%) [13,15,26], Iran (1/12, 8%) [27], Denmark (1/12, 8%) [28], China (1/12, 8%) [29], Nigeria (1/12, 8%) [30], Ireland (1/12, 8%) [31], Greece (1/12, 8%) [32], Finland (1/12, 8%) [33], Canada (1/12, 8%) [6], and Switzerland (1/12, 8%) [14]. Furthermore, 4 studies were conducted in >1 country, with 1 study conducted in the United States, India, Nepal, and Bangladesh [34]; 1 study conducted in the United States, Japan, Singapore, and the United Kingdom [12]; and 2 studies conducted worldwide [35,36].…”
Section: Location Of Included Studiesmentioning
confidence: 99%
“…However, the artificial intelligence technology and use of the tool were still through a website. Three studies described the development of tools that were not yet deployed [29,32,34]. Dhakal et al [34], Yu et al [29], and Heo et al [36] reported the development of a self-triage tool that appears to be independent of any health care system, although the tool in South Korea was reported to be used within the Korean military.…”
Section: Administration Of Toolsmentioning
confidence: 99%
“…Hence, there are potential symptom constellations that allow discrimination between the three diseases.The triage of patients with newly developed symptoms -any individual under suspicion of being at risk of SARS-CoV-2 infectionremains a challenge during this pandemic. Digital application-based symptom reporting and triage have been evaluated in prospective trials in the UK, China and the US [23][24][25]. The improvement of triage will also (i) enhance pre-test probability for SARS-CoV-2 PCR swabs or alternative test methods; (ii) increase the availability of tests in general to make current infection numbers more accurate; (iii) ease unnecessary quarantine; and (iv) reduce the closure of schools, child day care and public services.ARIA-MASK includes a decision-making tool for allergic rhinitis 14.…”
mentioning
confidence: 99%